The Administration of Corporate Social Responsibility in the District Regulation in Indonesia - Mukti Fajar ND (EUROPEAN CENTER FOR SCIENCE EDUCATION AND RESEA, 2015)
In Indonesia, Corporate Social Responsibility (CSR) is corporate activity that is regulated by the law. By means of the Investment Law No.25 year of 2007 and the Limited Liability Company Act No. 40 year of 2007, it is regulated that every company in Indonesia is obliged to implement CSR. However, these regulations are not set technically; therefore some local governments have made guidelines for the implementation of CSR through the District Regulations. The problems of this study are: (1) how is the CSR regulation model in the District Regulation? (2) What are the company’s attitude and the company’s request towards the CSR regulation in the District ? This study uses normative law research method that examines the provisions of the law, as well as empirical legal research method that used to observe the behavior and the attitude of the government and corporate actors. This research took place in several provinces in Indonesia.The results of this research are: First, the CSR regulation in regional area is formulated based on local government authorities. The provisions of these district regulations are customized to the interests of each region, although it still normatively refers to the standard legislation. Second: The Company’s attitudes prefer the self-regulated regulations arranged by their respective companies. Additionally, the setting of CSR can make the arrangement of CSR activities in accordance with the District Government program; as a result it can speed up the community development.